Development of male-larger sexual size dimorphism in a lizard: IGF1 peak long after sexual maturity overlaps with pronounced growth in males - Meter, Brandon; Kratochvíl, Lukáš; Kubička, Lukáš; Starostová, Zuzana (Frontiers in Physiology, 2022)
Squamate reptiles have been considered to be indeterminate growers for a long time. However, recent studies demonstrate that bone prolongation is stopped in many lizards by the closure of bone growth plates. This shift in the paradigm on lizard growth has important consequences for questions concerning the proximate causes of sexual size dimorphism. The traditional model on highly plastic and indeterminate growth would correspond more to a long-term action of a sex-specific growth regulator. On the other hand, determinate growth would be more consistent with a regulator acting in a sex-specific manner on the activity of bone growth plates operating during the phase when a dimorphism in size develops. We followed growth of males and females of the male-larger Madagascar ground gecko (Paroedura picta) and monitored activity of bone growth plates, gonad size, levels of steroids, and expression of their receptors (AR, ESR1, ESR2) and of genes from the insulin like growth factor network (IGF1, IGF2, IGF1R and IGF2R) in livers. Specifically, we measured gene expression before the onset of dimorphic growth, at the time when males have more active bone growth plates and sexual size dimorphism was clearly visible, and after a period of pronounced growth in both sexes. We found a significant spike in the expression of IGF1 in males around the time when dimorphism develops. This overexpression in males comes long after an increase in circulating testosterone levels and sexual maturation in males, and it might be suppressed by ovarian hormones in females. The results suggest that sexual size dimorphism in male-larger lizards can be caused by a positive effect of high levels of IGF1 on bone growth. The peak in IGF1 resembles the situation during pubertal growth spurt in humans, but in the lizards it seems to be sex-specific and disconnected from sexual maturation.